Effects of isonitrogenous and isocaloric total mixed ration composed of forages with different quality on milk fatty acid composition and gene expression of mammary lipogenic enzymes in mid‐lactating dairy cows. (16th December 2018) - Zhang, Hang; Ao, Changjin; Khas‐Erdene,; Dan, Ni
Abstract: The aim of this study was to determine the effects of isonitrogenous and isocaloric diets containing different qualities of forages and concentrate content on milk fat composition and genes that encode mammary lipogenic enzymes in dairy cows. A total of 20 Holstein cows were assigned to 1 of 2 treatment diets composed of either mixed forages (MF, starch : 21.50%) or corn stover forage (CS, starch : 25.39%). Mammary tissue biopsies were performed to analyze the mRNA expression of lipogenic enzymes. Dry matter intake, body weight, milk protein, and lactose were not affected by treatments. The milk yield, fat content and saturated fatty acid (SFA) and short‐ and medium‐chain fatty acid (SMFA) contents in milk were lower in the CS diet than in the MF diet, but the unsaturated FA and long‐chain FA contents were higher. Genes involved in de novo FA synthesis, FA uptake and transport, and Δ9‐desaturation were lower in the CS treatment than in the MF treatment. No effects on the nuclear transcription factors were observed between the two treatments. The data indicated that corn stover diet reduced the milk yield, fat content, SMFA, and SFA contents in milk, as well as the gene expression of mammary lipogenic enzymes in dairy cows.